(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ In this research paper, the electrical and radiation characteristics of a proposed fractal antenna based on the Koch curve in the second iteration for reception of digital terrestrial television signals are designed and analyzed by laboratory tests. Methodology/approach/design ”“ The design is based on the concepts of fractal geometry and on a previously designed antenna, which is adapted to obtain a different frequency of operation; the designed antenna is constructed in three different ways, finally, they are tested in the lab using vector-network-analyzer, that allows to measure parameters, such as: VSWR, gain and radiation pattern. Findings ”“ The fractal antenna based on the Koch curve has the necessary characteristics to receive digital terrestrial television signals in the UHF band.